Aqueous OH−/H+ Dual‐Ion Zn‐Based Batteries. Issue 4 (8th August 2022) - Cai, Pingwei; Chen, Kai; Lu, Zhiwen; Mondal, Ritwik; Thotiyl, Musthafa Ottakam; Wen, Zhenhai
Abstract: Aqueous Zn‐based batteries hold multiple advantages of eco‐friendliness, easy accessibility, high safety, easy fabrication, and fast kinetics, while their widespread applications have been greatly limited by the relatively narrow thermodynamically stable potential windows (i. e., 1.23 V) of water and the mismatched pH conditions between cathode and anode, which presents challenges regarding how to maximize the output voltage and the energy density. Recently, aqueous OH − /H + dual‐ion Zn‐based batteries (OH − /H + ‐DIZBs), where the Zn anode reacts with hydroxide ions (OH − ) in alkaline electrolyte while hydrogen ions (H + ) are involved in the cathode reaction in the acidic electrolyte, have been reported to be capable of broadening the working voltage and improving the energy density, which offers practical feasibility toward overcoming the above limitations. This Review thus takes this chance to investigate the recent progress on aqueous OH − /H + ‐DIZBs. First, the concept and the history of such OH − /H + ‐DIZBs are introduced, and then special emphasis is put on the working mechanisms, the progress of the development of new batteries, and how the electrolytes improve their performance. Finally, the challenges and opportunities in this field are discussed. Abstract : Duality : This is the first Review of OH − /H + dual‐ion Zn‐based batteries (OH − /H + ‐DIZBs) that are operated in alkaline and acidic electrolytes. The concept, history, development, current research status, and the challenges are summarized, and the working principles and cathode materials are highlighted.